2016
DOI: 10.4102/jef.v9i3.65
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price Shocks and Economic Activity: The Asymmetric Cointegration Approach in South Africa

Abstract: This study examines the link between oil prices and economic activity proxied by gross domestic product in the context of South Africa. The study employs the asymmetric approach proposed by Schorderet (2004) and advanced by Lardic and Mignon (2008). Asymmetric cointegration is used because it is believed that increasing and decreasing oil prices do not have similar or equal impacts on economic activity. In this study we document evidence for an asymmetric response of economic activity to oil price shocks. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The study also shows that increasing oil prices and GDP are positively correlated. [49] examined the relationship between economic activities and changes in oil prices in South Africa; the results indicate that both increasing and decreasing oil prices are important because they have asymmetric impacts on economic activities. [53] concluded that there is a relationship between the macroeconomic variables and oil price fluctuations and that Nigeria is highly vulnerable to changes in oil prices.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also shows that increasing oil prices and GDP are positively correlated. [49] examined the relationship between economic activities and changes in oil prices in South Africa; the results indicate that both increasing and decreasing oil prices are important because they have asymmetric impacts on economic activities. [53] concluded that there is a relationship between the macroeconomic variables and oil price fluctuations and that Nigeria is highly vulnerable to changes in oil prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[53] concluded that there is a relationship between the macroeconomic variables and oil price fluctuations and that Nigeria is highly vulnerable to changes in oil prices. However, most of these related studies focused mainly on the impact of increasing oil prices on developed and oil-importing nations, such as [5], [49], [6], [66], [33], [39], [71], [11], [48], [27], [63], [4], [17], [18], [8], [19], [10], [26], [24], [25], [23], [22], [21], [20], [34], [43]. Others still are mainly historical like those of [16], [28], [42], [64], [67].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bohi (1991) also argued that the oil price does not have any substantial macroeconomic effects by themselves. Nzimande and Msomis (2016) on examining oil price changes and economic activity in South Africa suggests that both increasing and decreasing oil price shocks are important as they both have asymmetric impacts on economic activities. Hamilton contends that increasing oil price is much more important in predicting the GDP of an economy rather than oil price decreases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, oil related studies are not new, given all the literature reviewed but majority of the examined economies are developed and oil importing (Mohaddes and Raissi, 2015;Taghizadeh-Hesary and Yoshino 2015;Hamilton and Herrera, 2004). Other related studies lay more emphasis on the impact of increasing oil price on the examined economies (Kilian, and Lutkepohl, 2016;Nzimande and Msomis, 2016;Taghizadeh-Hesary and Yoshino 2015;Kaplan, 2015;Eltejaei, 2015;Dizaji, 2014;Hamilton, 2005;1983;Kilian 2009). Some other related studies are mainly historical as the findings and conclusions are based on previous studies (Eze and Kouhy, 2021;Husain et al, 2015;Adamu, 2015;Yanar, 2014Yanar, , 2009.…”
mentioning
confidence: 99%
“…Hamilton, (1996) argues that oil price increase only matters when they are large enough about the previous experience. Nzimande and Msomis (2016) on examining oil price changes and economic activity in South Africa suggests through the findings that both positive and negative oil price shocks are important as they both have asymmetric impacts on economic activities.…”
Section: Introductionmentioning
confidence: 99%